Synthesis and Characterization of Zero Valent Iron Prepared Using Green Synthesis Method - Devi Indrawati Syafei; Sahid Hidayat; Yusmaniar (Chemistry and Materials, 2022)
This research was conducted to develop a green synthesis method for zero valent iron (ZVI) preparation. The ZVI was synthesized by reacting FeCl2 with polyphenols extracted from kepok banana peels. This polyphenol extraction process was carried out using three different solvents, namely: water, chloroform, and ethyl acetate. Gas chromatography mass spectroscopy test showed three main phenolic compounds contained in the banana peel extract, namely: 2-methoxy-4-vinylphenol, 4-methoxy-2-vinylphenol, and 2-methoxy-5-vinylphenol. The optimum composition of FeCl2 and polyphenol was 3:2. Fourier transform infra red spectroscopy data confirmed that the synthesized ZVI contains organic compounds having –OH and C=O groups which are assumed to be capping agents that can maintain stability. This has also been supported by the results of the energy dispersive X-ray analysis where there are carbon atoms (C) and oxygen atoms (O) in ZVI. The ZVI particle size was uneven and form a compact solid. The largest particle size distribution of ZVI is in the range of 234.49 nm - 407.49 nm with the average size of ZVI beings 616.26 nm. The results of the XRD analysis have also confirmed the formation of a simple cubic ZVI with fine crystallite size of ca 26.64 nm.